Environmental Crimes and Green Justice under India’s Bharatiya Nyaya Sanhita and BNSS - Neeraj Kumar; Sourabh Sri Mala (Mabadi Iqtishad Al Islami, 2026)
The enactment of the Bharatiya Nyaya Sanhita, 2023 (BNS) and the Bharatiya Nagarik Suraksha Sanhita, 2023 (BNSS) represents a significant transformation in India’s criminal justice system. Although environmental protection in India has traditionally been governed by specialized environmental statutes, the newly enacted criminal laws also contain provisions capable of addressing environmental crimes and ecological harm. This article examines the role of the BNS and BNSS in promoting environmental accountability and strengthening green justice within India’s legal framework. The study adopts a doctrinal and analytical legal research methodology based on statutory interpretation, constitutional analysis, and judicial precedents. The research finds that provisions relating to public nuisance, water pollution, atmospheric contamination, hazardous substances, and acts likely to spread disease collectively establish a broader criminal law framework for environmental protection. Judicial interpretation of Article 21 of the Constitution, together with principles such as the polluter pays principle, precautionary principle, and sustainable development, has further strengthened environmental jurisprudence in India. The article argues that the BNS and BNSS contribute toward mainstreaming environmental protection within criminal law, but effective enforcement, institutional coordination, and stronger implementation mechanisms remain necessary for achieving sustainable environmental justice.